Kandilarya - Aliposa, Jericho Sandino R. 1988-; Santiago, Arminda V.; University of the Philippines. College of Mass Communication (2013)
"There are certain issues in the Philippines that need to be examined more. These issues relates mostly to social struggles that are inherent in all societies around the world. It is in this light that the filmmaker wishes to examine the indigenous aspect of such social struggles. Kandilarya is a documentary film that explores how skilled workers and their products are imbued with value with their craft and industry and, at the same time, how their skill and craft can keep them trapped in a system that exploits them. The film aims to put into discursive light the issues on the value of labor, compensation, exploitation, and family relations in the social, political, and economic context within an industrial space. Using the reflexive mode of documentary, the filmmaker offers an alternative narration of the subject not through dialogues or talking heads but through movement, motifs, and rhythm."
Vita.
Thesis (A.B. Film and Audio-visual Communication)--University of the Philippines Diliman
Keywords: Candle making; Motion picture authorship; Social classes in motion pictures; Social problems in motion pictures; Working class in motion pictures